Financial Reform : What Shakes it? What Shapes it? - Mody, Ashoka (IMF Working Papers; Working Paper ;, 2003)
Despite stops, gaps, and reversals, financial reforms advanced worldwide in the last quarter century. Using a new index of financial liberalization, we conclude that influential events shook the status quo, inducing both reforms and reversals, while learning, more so than ideology and country structure, shaped and sustained widespread reforms. Among shocks, a decline in global interest rates and balance of payments crises strengthened reformers; banking crises were associated with reversals, while new governments brought about both reforms and reversals. Learning occurred domestically-initial reforms raised the likelihood of further reforms-and through observing regional reform leaders. Among structural features, greater openness to trade appears to have increased the pace of financial reform.